The physical demands in elite women's soccer training in Portugal - Fernandes, Renato (2021)
Currently, elite women’s soccer players are exposed to greater training volume and competition demands than ever before. Consequently, these increased physical requirements may have implications for both physical performance levels and injury patterns. This study, which is a small part of a bigger project, aims to study the physical demands on the elite women soccer training using the External Load.